Security Analyst Multi-Year Earnings Forecasts and the Capital Market (Book). - Hendrickson, Harvey S.; Hopwood, William S. (The Accounting Review, 1986)
Reviews the book "Security Analyst Multi-Year Earnings Forecasts and the Capital Market," by Philip Brown, George Foster and Eric Noreen.